1976
DOI: 10.1128/aem.32.5.716-722.1976
|View full text |Cite
|
Sign up to set email alerts
|

Timed-release capsule method for coliform enumeration

Abstract: Wax-coated capsules containing selective ingredients (brilliant green and oxgall) were added at the time of inoculation of most-probable-number media (modified lactose broths). The inhibitory ingredients gradually diffused from the capsules into the nonselective media, imparting selectivity to the media. Concentrations of brilliant green did not reach inhibitory levels until 2 or more h had elapsed, which permitted repair of some injured cells. Resuscitation of heatinjured Escherichia coli B cells occurred in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1977
1977
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The feasibility of combined procedures for use in microbial assays has been demonstrated here and by Lanz and Hartman (11). We hope that others will be stimulated to substantiate the present results, improve upon the combined procedures, and possibly devise other applications of the same principle.…”
Section: Discussionsupporting
confidence: 69%
“…The feasibility of combined procedures for use in microbial assays has been demonstrated here and by Lanz and Hartman (11). We hope that others will be stimulated to substantiate the present results, improve upon the combined procedures, and possibly devise other applications of the same principle.…”
Section: Discussionsupporting
confidence: 69%
“…Alford & Knight (1969) delayed the addition of selenite to selenite cystine broth until 4 h after incubation had commenced. They found that the efficiency of isolation of salmonellas was similar to that achieved by using an overnight pre-enrichment followed by 24 h enrichment procedure with the bonus that the time taken to complete the examination of samples was reduced by 1 d. Similar procedures utilizing wax-coated capsules containing selective agents have been utilized in the examination of water and foods for coliforms and salmonellas (Lanz & Hartman 1976).…”
Section: Resuscitation or Pre-enrichment Conditionsmentioning
confidence: 86%
“…typhi (Harvey & Price 1964). The performance of some of these media has been investigated but with no overall agreement (Wells et al 1958;Montford & Thatcher 1961;Guinee et al 1965;Kumar et al 1971Kumar et al , 1972Carlson & Snoeyenbos 1974;Fagerberg & Avens 1974, 1976.…”
Section: Enrichment Mediamentioning
confidence: 99%
“…Trypticase soy broth (TSB) or agar (TSA) have been used as the repair media prior to culturing in lauryl sulfate tryptose broth (LST) or on violet red bile agar (VRBA) (Warseck et al 1973;Speck et al 1975). Another procedure has been to add time-release capsules containing inhibitors (brilliant green and oxgall) to lactose broth to impart selectivity to the medium following repair (Lanz and Hartman 1976).…”
Section: Introductionmentioning
confidence: 99%